STRATEGI DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP PENINGKATAN PENJUALAN HUNIAN HOMESTAY DI HUTA SIALLAGAN, KABUPATEN SAMOSIR - Sinurat, Christin Witasari (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This study aims to analyse the effect of digital marketing strategies and service quality on increasing homestay sales in Huta Siallagan, Samosir Regency. Huta Siallagan is a tourist village known for its rich Toba Batak culture and is a popular tourist destination. However, homestay managers in this area face challenges in increasing sales amid increasingly fierce competition. Therefore, this study examines two important factors: digital marketing strategy and service quality, which contribute to increasing sales. The research method used is quantitative method with saturated sampling technique. The respondents of this study were 30 homestay managers or owners in Huta Siallagan. Data were collected through questionnaires that included digital marketing strategy variables (X1) and service quality (X2), as well as the dependent variable of sales increase (Y). Data analysis was conducted using multiple linear regression tests, t tests, F tests, and coefficients of determination to measure the influence of each variable. The results showed that digital marketing strategies and service quality significantly influenced the increase in homestay sales. Partially, digital marketing strategy has a more dominant influence than service quality, although both contribute positively. In the coefficient of determination, these two variables contributed 84.5% to the increase in homestay sales. In conclusion, the synergy between effective digital marketing strategies and good service quality is essential to increase homestay sales in Huta Siallagan. Therefore, homestay managers need to optimise these two aspects in order to compete and increase revenue in the tourism industry.